Planothidium incuriatum sp. nov. a widely distributed diatom species (Bacillariophyta) and type analysis of Planothidium biporomum - Wetzel, Carlos E.; de Vijver, Bart Van; Hoffmann, Lucien; Ector, Luc (Phytotaxa, 2013)
Planothidium incuriatum sp. nov. is described from freshwater samples from Europe and South America. It is compared with the type material of Achnanthes biporoma (=Planothidium biporomum), described from North America, to differentiate it from the new, related species. Species morphologies were compared using both light and scanning electron microscopy. Planothidium incuriatum can be differentiated from P. biporomum by its valve outline with more rostrate apices (instead of capitate) and by the areolation pattern of the striae in the raphe less valve (higher number of rows of areolae per stria). Distribution of P. incuriatum was determined from worldwide iconographic literature records where it was often identified as Planothidium biporomum among other names here detailed. While P. incuriatum appears to be widely distributed around the world, P. biporomum is, according to verified records, far more restricted.